Nyèn kal ngisidang bangkéné? Shifting Relations of Neighborliness and Family in Bali - Richard Fox (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
Balinese forms of social organization, collective labor and solidarity are gradually being transformed – and often displaced – by new social institutions and their attendant ideals, desires and pleasures. The rise of the nuclear family, as a new social ideal and institution, is one the more important developments in this connection. This essay examines rival conceptions of the family, and of household economy, that underpinned a debate that took place in a southerly Balinese ward over the provision of neighborly assistance during six-monthly odalan ceremonies. The analysis provides insight into how social and cultural transformation is understood and experienced at the level of day-to-day life.